Culture shock Overseas Student at OISCA (Organization for Industrial, Spiritual, and Cultural Advancement) Sukabumi Training Center - Tresnasari, Ningrum; Fithria, Ilma; Farhi Saudi, Hammad (International Journal of Psychosocial Rehabilitation, 2020)
OISCA Overseas Students are people who leave their home regions to attend training at a Training Center institution that has implemented a system such as in Japan to familiarize their students before they leave for Japan. The types and adaptation strategies of overseas students in the OISCA environment are interesting objects to study. This study aims to determine the type of culture shock experienced by OISCA overseas students during the main training at OISCA and to find out the adaptation strategies they have taken to overcome the culture shock. The object of research was 48 OISCA overseas students who were attending the main training at OISCA. The process of collecting data is done using the questionnaire method. Culture shock experienced by OISCA students is related to the factors of discipline, independence, socialization and physical change. The cause of culture shock is the lack of awareness of Japanese time and work ethic. Adaptation strategies undertaken by overseas students at OISCA include familiarizing themselves with the new environment, being open, being professional, and making preparations before serving.